Optimization and evaluation of textural properties of ultra-filtrated low-fat cheese containing galactomannan and Novagel gum - Sharafi, Sharmineh (Array, 2019)
The general aim of this research was to optimise textural properties and to evaluate the possibility of producing ultra-filtrated low-fat cheese (7-9 % (w/w)), containing various concentrations of galactomannan and Novagel (0.1-0.5 % w/w), and assessing textural properties of produced low-fat cheeses and comparing them with full fat ones. According to the results, reducing fat implies increasing the hardness, cohesiveness, gumminess and chewiness of the tested samples. On the other hand, adding galactomannan gum and Novagel, and increasing their concentration, implies reducing all of the above mentioned textural properties. According to the results, increasing the amount of fat and using galactomannan and Novagel gum, implies increasing the adhesiveness and springiness of the tested treatments. The results showed that textural properties including hardness, adhesiveness, cohesiveness, gumminess and chewiness, of sample containing 9 % (w/w) fat, 0.5 % (w/w) galactomannan, and 0.3 % (w/w) Novagel were not of significantly different from the control sample and was selected as the superior sample. Multiple optimization of the low-fat cheeses textural properties via Response Surface Method (RSM) software showed that the treatment containing 9 % (w/w) fat, 0.1 % (w/w) Novagel and 0.46% (w/w) galactomannan fulfils 84 % of desirable properties of a full fat cheese.